Pengembangan Science Mobile App Berbasis Masalah untuk Meningkatkan Kemampuan Berpikir Kritis dan Literasi Digital - Indri Nurwahidah; Yeni Widiyawati; Dwi Septiana Sari (Postgraduate, University of Mataram, 2025)
The use of technology in the learning process can support 21st century learning. The purpose of this study is to determine the feasibility of a problem-based science mobile app to improve students' critical thinking skills and digital literacy, to determine students' responses to a problem-based science mobile app to improve students' critical thinking skills and digital literacy. The method used is research and development (R&D). The stages carried out adapt the Borg & Gall model, namely preliminary studies, planning, initial product development, product validation, limited trials, revisions to produce the main product, and product dissemination and implementation. The results of the study showed an average total validation score from media experts, material experts and teachers/practitioners in the learning aspect of 52.17, material aspects 54.17, media display aspects 77.33, and programming aspects of 43.17, all aspects of the very good category. The results of the analysis of student responses to the problem-based science mobile app obtained an average score of 14.39 in the very good category. Based on the results of the study, it can be concluded that the developed problem-based Science Mobile App is suitable for use by teachers as a medium to improve critical thinking skills and digital literacy. Student response to the problem-based science mobile app was very good, so the app can be used well by students.